A new speech discrimination test in Tamil - Samuel, Jesudas Dayalan (Journal of All India Institute of Speech and Hearing)
Speech audiomttry is an indispensable clinical tool of audiological evaluation. ,;·tts assistance in measurifhgJ hea;ing acuity, determining the anatomIc location’ of the hearin; disord r and in ,evall:lation of ability’ to comlnunicate is’ well known. Non-availability ofproperly prep ed ,’ sp ech materials in particuiar Indian la guag s is a well kno v’n faci